Perceptions of measles, pneumonia, and meningitis vaccines among caregivers in Shanghai, China, and the health belief model: a cross-sectional study - Abram L. Wagner; Matthew L. Boulton; Xiaodong Sun; Bhramar Mukherjee; Zhuoying Huang; Irene A. Harmsen; Jia Ren; Brian J. Zikmund-Fisher (BMC, 2017)
Abstract Background In China, the measles vaccine is offered for free whereas the pneumococcal vaccine is a for-fee vaccine. This difference has the potential to influence how caregivers evaluate whether a vaccine is important or necessary for their child, but it is unclear if models of health behavior, such as the Health Belief Model, reveal the same associations for different diseases. This study compares caregiver perceptions of different diseases (measles, pneumonia and meningitis); and characterizes associations between Health Belief Model constructs and both pneumococcal vaccine uptake and perceived vaccine necessity for pneumonia, measles, and meningitis. Methods Caregivers of infants and young children between 8 months and 7 years of age from Shanghai (n = 619) completed a written survey on their perceptions of measles, pneumonia, and meningitis. We used logistic regression models to assess predictors of pneumococcal vaccine uptake and vaccine necessity. Results Only 25.2% of children had received a pneumococcal vaccine, although most caregivers believed that pneumonia (80.8%) and meningitis (92.4%), as well as measles (93.2%), vaccines were serious enough to warrant a vaccine. Perceived safety was strongly associated with both pneumococcal vaccine uptake and perceived vaccine necessity, and non-locals had 1.70 times higher odds of pneumonia vaccine necessity than non-locals (95% CI: 1.01, 2.88). Conclusions Most factors had a similar relationship with vaccine necessity, regardless of disease, indicating a common mechanism for how Chinese caregivers decided which vaccines are necessary. Because more caregivers believed meningitis needed a vaccine than pneumonia, health care workers should emphasize pneumococcal vaccination's ability to protect against meningitis.